The onward workbook : daily activities to cultivate your emotional resilience and thrive - Aguilar, Elena, 1969- 4 0 16; 5 (San Francisco, CA : Jossey-Bass, a Wiley brand, 2018)
An empowering journey that keeps great teachers in the classroom The Onward Workbook is a collection of tools and strategies that help teachers banish the burnout and cultivate true resilience. Keyed to the framework presented in Onward, this companion piece augments the text with practical exercises, coaching, and step-by-step walkthroughs of beneficial practices. Deep introspection allows you to verbalize your feelings, name your challenges, and identify the tools you have and the tools you need-from there, you'll explore each of the 12 Key Habits and learn how to put them into practice every day. In cultivating resilience within yourself and your teaching practice, you improve your health, your outlook, and your relationships while building an environment in which every child succeeds. This workbook takes you on a journey of specific self-discovery that changes your perspective, renews your confidence, and empowers you to make the much-needed changes that allow you to continue inspiring young minds. -Dig deeper within to discover what you're truly made of -Decode complex emotions, body language, and nonverbal communications -Challenge your beliefs, build community, and navigate difficult interactions -Learn more, feel more, play more, and practice effective self-care Resiliency is an underrated skill-one that can make all the difference in our schools. Challenges will always arise, but it is your response that dictates the outcome. Can you think of a more important lesson for your students' When some 70 percent of teachers quit within their first five years, it is clear that changes must be made. The Onward Workbook equips you to make the changes that you can, and flourish into the future. While this book can be used by individuals, it is also designed so that groups, teams, departments, or an entire staff can take up the learning together. There are specific suggestions in the workbook for using this with a group, and educators will reap even more reward from discussing the practices and experiences with colleagues.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed March 28, 2018).
Keywords: 2 -- 0; 6; Resilience (Personality trait);Self-actualization (Psychology);Resilience (Personality trait).;Self-actualization (Psychology). -- Problems, exercises, etc.;Problems, exercises, etc; 20; Electronic books.;Problems and exercises